Childhood and the Display of Violence in Contemporary Museum Exhibitions on Argentine State Terrorism - Perez, Mariana Eva (2023)
This contribution sets out to investigate the inclusion of childhood experiences of state violence in museum narratives displayed in former clandestine detention centres set up by the last Argentine dictatorship (1976–1983) and later reconverted into memorial spaces and museums. In a comparative analysis, we examine three different curatorial approaches to this topic, discussing the strategies deployed to represent these experiences: the permanent exhibition at the ESMA Museum and Site of Memory, the “virtual museum” Proyecto Tesoros [Treasures Project], by Colectivo de hijos (Cdh) [Collective of Children], and a temporary exhibition entitled ¿Aquí hubo niñ@s? [Were There Children Here?] at the former Olimpo. We furthermore discuss a new perspective that has not so far been acknowledged in museological exhibition practice in post-dictatorship Argentina: the affective response by visitors to the representation of children as survivors of the dictatorship.